The Constitutional Court : A Guarantee for Protecting the Right to a Healthy Environment - GHAOUAS, Hassina; HADJI, Ibtissem (Journal of Human Sciences, 2025)
The environment holds immense importance, having become a subject of third-generation rights recognized internationally through various treaties and conventions, which has transitioned to constitutions and internal legislation. Thus, the Algerian constitutional founder enshrined this right within the constitutional document starting from the 2016 constitutional amendment and reaffirmed the same approach through the 2020 amendment, reinforcing it with significant constitutional guarantees, the most important of which is replacing the Constitutional Council with the Constitutional Court as a strong guarantee for the protection of rights and freedoms, including the right to a healthy environment. This is done by enabling litigants to challenge the unconstitutionality of any legislative or regulatory text that violates this right, in addition to the oversight and interpretive role it plays in this regard.